Ecosystem services may provide large economic values in forests in Kenya and Vietnam - Hettiarachchi, Upeksha; Davis, Kristin E.; Zhang, Wei (CGIAR, 2024)
A conservative estimate suggests forests provide services worth $25.78 billion for Kenya and $35.60 billion in Vietnam annually in 2022 US dollars. The findings provide a crucial defense against deforestation and degradation because of the costs associated with these threats. While more information is needed to understand the full value of forests’ ecosystem services, these estimates can be of great utility to policymakers and nature-positive decision-making.